Formulation and evaluation of a bifonazole-loaded chitosan-honey invasomal hydrogel for enhanced topical antifungal activity - Patil, Shivaji; Bhargav, Sushil (Creative Pharma Assent, 2025)
Background: To develop a novel bifonazole-loaded chitosan-honey invasomal hydrogel to improve the drug's topical antifungal efficacy. In this formulation, invasomal vesicles, composed of phospholipids, ethanol, and terpenes, were utilized to enhance the penetration of bifonazole through the skin. Methodology: These invasomal carriers were incorporated into a chitosan-based hydrogel matrix, which provided structural stability and bioadhesive properties, allowing for better retention on the skin. Additionally, natural honey, known for its antibacterial and wound-healing properties, was included to enhance the therapeutic benefits of the hydrogel. Results & Discussion: Invasomes were prepared using soya phosphatidylcholine, ethanol (30% v/v), and d-limonene (0.5%) and then incorporated into a chitosan-honey gel matrix. Among the six formulations (IF1–IF6), IF5 showed optimal results, with 93.32% drug release over 12 hours, a viscosity of 6545 ± 26 cps, a pH of 6.85, and antifungal inhibition zones of 17 mm (Candida albicans) and 11 mm (A. flavus). The formulation was characterized in terms of its physical properties, including viscosity, gel strength, and spreadability, and evaluated for its drug entrapment efficiency, in vitro drug release profile, and ex vivo skin permeation. This study demonstrates a synergistic system enhancing skin permeation, drug retention, and antifungal efficacy. Conclusion: This formulation represents a promising alternative for the effective and patient-friendly treatment of superficial fungal infections, offering improved drug delivery, enhanced therapeutic efficacy, and a reduced dosing frequency.